Factors Influencing Students Choice of Pursuing Nursing Education in Nepal - Shrestha, Kalpana; Sapkota, Abja (Nepal Medical College Journal, 2021)
Nursing is a caring and helpful profession and the unique function of the nurse is to assist the individual, sick or well. Although nursing, as an education and a career, is on a rising trend in Nepal, there is paucity of data regarding the factors that influence choosing it. So, a cross sectional study was carried out purposively among first year nursing students who were just enrolled to study nursing in different nursing colleges in Kathmandu Valley, Nepal. Structured questionnaires were distributed among 336 nursing students. Major source of inspiration to pursue nursing were their parents. The main reasons to choose nursing are to learn new things and to secure job. Major factors which contributed getting enrolled into nursing was an opportunity to care and help needy people (μ±σ=3.8±.39) and an attraction towards possibilities of working abroad in the future (μ±σ=3.4±.59). Besides, the students also felt that nursing was a noble and respectable profession where they could learn newer technologies with a better advancement. About 45.8% agreed that nursing was a profession with relatively lesser earnings and almost 40.5% disagreed that the cost of nursing education was within their payable range.It is recommended that nurses should be well paid and the vacant positions need to be fulfilled in time in both government and private sectors to motivate young students. In addition, it is time to bring advancement in their career by initiating and expanding further courses in nursing education and practice like nurse practitioner, specialization degrees and PhD inside the country.